Triggers and Priority: An Integrated Model of the Effects of Bankruptcy Law on Overinvestment and Underinvestment - Daniel E. Ingberman (Washington University Law Quarterly, 1994)
Specifically, in this Article two dimensions of investment are considered: (1) the firm's choice of capitalization or its capital-intensity of production (including the amount of capital invested in the firm, and the debt/equity mix); and (2) given the firm's choice of capitalization, its choice among alternative investment opportunities. Dimension (1) covers what is usually referred to as the "underinvestment" problem by characterizing the firm's endogenous choices of debt and equity capital. Dimension (2) covers what is usually referred to as the "overinvestment" problem by characterizing the use to which the firm applies any amount of capital.
Keywords: Bankruptcy law; United States; Bankruptcy; Investments